Upaya IOM (International Organization for Migration) dalam Menangani Kasus Human Trafficking di Indonesia Tahun 2017-2022 - Eriston Saragih & Alfajri (UIR Press, 2022)
This research discusses the efforts of IOM (International Organization for Migration) in handling Human Trafficking cases in Indonesia from 2017 to 2022. This problem examines the organization's way of dealing with Human Trafficking in Indonesia. The rise of human trafficking in Indonesia is an example of transnational crime. It directly impacts and risks the security of every individual Indonesian citizen. IOM as an international organization plays a role in protecting migrants and victims of human trafficking, as well as raising public awareness regarding the risks and impacts of human trafficking. This research uses a qualitative research method by describing the author's knowledge of the topic being researched, supported by statements from previous authors with relevant topics. This discussion uses Clive Archer's concept of international organizations as Instruments, Arenas, and Actors. IOM's efforts include cooperation with relevant agencies, implementation of training and mentoring programs, and campaigns to increase public understanding. Despite several challenges, IOM remains committed to protecting migrants and victims of human trafficking and increasing law enforcement efforts against perpetrators.